Gastrointestinal bleeding as debut of complicated celiac disease - Albán, Ronald (2024)
Celiac disease (CD) is an autoimmune  malabsorption syndrome that presents with intolerance to gluten (gliadin), a protein  found in wheat. The most common symptoms are diarrhea, steatorrhea, weight loss, weakness, vitamin and mineral deficiency. The probability of developing complicated CD is relatively  low, among its main manifestations we have refractory sprue, T-cell lymphoma and ulcerative jejunitis (UY) of which a few cases develop gastrointestinal bleeding. Furthermore, we  present the case of a 51-year-old patient who developed intestinal hemorrhage due to complicated CD, where upper digestive video endoscopy (VEDA), video colonoscopy (VCC),  capsule endoscopy (CE) and biopsy of the jejunum and ileum were performed  confirming the diagnosis of CD along with ulcerative jejunoileitis.